2021
DOI: 10.1038/s41467-021-25710-4
|View full text |Cite
|
Sign up to set email alerts
|

TNF-α-mediated m6A modification of ELMO1 triggers directional migration of mesenchymal stem cell in ankylosing spondylitis

Abstract: Ankylosing spondylitis (AS) is a type of rheumatic disease characterized by chronic inflammation and pathological osteogenesis in the entheses. Previously, we demonstrated that enhanced osteogenic differentiation of MSC from AS patients (AS-MSC) resulted in pathological osteogenesis, and that during the enhanced osteogenic differentiation course, AS-MSC induced TNF-α-mediated local inflammation. However, whether TNF-α in turn affects AS-MSC remains unknown. Herein, we further demonstrate that a high-concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(50 citation statements)
references
References 59 publications
(113 reference statements)
3
47
0
Order By: Relevance
“…AS is an autoimmune disease with poorly-defined etiology and pathogenesis ( 70 72 ). Thus, more effort is needed to elucidate the underlying pathobiology so as to develop novel, mechanism-driven therapeutics.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…AS is an autoimmune disease with poorly-defined etiology and pathogenesis ( 70 72 ). Thus, more effort is needed to elucidate the underlying pathobiology so as to develop novel, mechanism-driven therapeutics.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…For instance, Liu et al discovered that METTL3 promoted BMSCs osteogenesis by mediating m6A methylation of BMP2 transcripts and supposed that METTL3 could mitigate ovariectomy-induced osteoporosis [ 29 ]. Xie et al revealed that TNF-α induced m6A modification in ELMO1 3′UTR triggers directional migration of mesenchymal stem cell in ankylosing spondylitis patients [ 30 ]. Wang et al elucidated a new pathogenesis of osteoporosis, that is, FTO mediates Runx2 mRNA demethylation to inhibit the osteogenic differentiation of BMSCs [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…The analyses indicated that the YTHDF2 and ALKBH5 mRNA expression in PBMC from patients with AS was significantly lower than in cells from the HC, whereas the mRNA expression of FTO , WTAP , METTL3 , and METTL14 was unchanged. Recently, Xie et al explored the level of ALKBH5, FTO, WTAP, METTL3, and METTL14 in MSC with or without tumor necrosis factor alpha (TNF-α) stimulation from patients with AS and showed inconsistent results that only METTL14 was clearly downregulated in MSC from AS ( 21 ). The causes for the conflicting consequences may be due to discrepancies in cell type and TNF-α stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, m6A modification and differential expression of key m6A regulators could use as diagnostic, prognostic, and therapeutic targets for many diseases ( 18 20 ). Moreover, Xie et al demonstrated that METTL14-dependent m6A modification of ELMO1 contributes to the directional migration of mesenchymal stem cell (MSC) in AS ( 21 ). Although the m6A modification can affect the function of MSC in AS, the feature of m6A modification in peripheral blood mononuclear cells (PBMCs) in human AS is still unclear.…”
Section: Introductionmentioning
confidence: 99%